Perbandingan Jumlah Booking Corporate Event antara High season dan Low season Tahun 2023–2025 di The Trans Resort Bali: Studi Kuantitatif dan Kualitatif - Ni Kadek Devi Citra Dewi; Ni Nyoman Teristiyani Winaya; Ida Bagus Sanjaya (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to compare the number of corporate event bookings between the high season and low season periods from 2023 to 2025 at The Trans Resort Bali, while identifying the factors influencing these differences and the strategies implemented to increase bookings during the low season. A mixed-methods approach was employed by integrating quantitative and qualitative analyses. The quantitative data consisted of 36 corporate event booking records collected during 2023–2025 and were analyzed using descriptive statistics, normality and homogeneity tests, and an Independent Samples t-test. Qualitative data were obtained through interviews, observations, and document analysis, followed by analysis using the Miles and Huberman interactive model with source and method triangulation to ensure data credibility. The quantitative findings indicate no statistically significant difference in the number of corporate event bookings between the high season and low season periods (p = 0.660), although the average number of bookings was slightly higher during the high season. The qualitative findings reveal that economic conditions are the primary factor influencing corporate event bookings, whereas public holidays, major festivals, and tourism demand have relatively limited effects because most corporate events are scheduled well in advance. To maintain stable booking performance, The Trans Resort Bali implements integrated event promotion, flexible meeting package development, and strategic partnerships with corporations, event organizers, and business partners. These findings provide practical insights for strengthening MICE marketing strategies and sustaining corporate event performance throughout the year.